Reassessing overlooked information about the diagnosis of Brachycephalus atelopoide (Anura: Brachycephalidae), a neglected problem for the taxonomy of the genus - Bornschein, Marcos R. [UNESP] (2021)
Fundação Grupo Boticário de Proteção à Natureza